2022
DOI: 10.31949/jcp.v8i4.2792
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Siswa Terhadap Pemanfaatan Kahoot Dan Quizizz Dalam Pembelajaran Di Kelas Iv Sekolah Dasar

Abstract: Penelitian ini bertujuan untuk mengetahui persepsi siswa terhadap pemanfaatan Kahoot dan Quizizz dalam pembelajaran di kelas IV SD. Penelitian ini menggunakan metode penelitian deskriptif kuantitatif dengan desain survey. Instrumen yang digunakan adalah angket. Populasi dalam penelitian ini yaitu seluruh siswa kelas IV Sekolah Dasar di Kecamatan Kalideres. Dengan teknik pengambilan sampel menggunakan teknik Cluster Random Sampling. Diperoleh sampel sebanyak 117 siswa. Analisis data ini menggunakan skala likert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…With the research conducted by Yhadi and Purwa, it can be concluded that the Kahoot application has a good impact on students who use it in terms of benefits. In other research conducted by Fadly and Sari, the study showed that the results of student perceptions of the Kahoot application were 71.1 and in the quizizz application were 69.5 (Fadly & Sari, 2022). It can be concluded that students prefer learning in the form of using Kahoot media than using media with quizizz.…”
Section: Introductionmentioning
confidence: 64%
“…With the research conducted by Yhadi and Purwa, it can be concluded that the Kahoot application has a good impact on students who use it in terms of benefits. In other research conducted by Fadly and Sari, the study showed that the results of student perceptions of the Kahoot application were 71.1 and in the quizizz application were 69.5 (Fadly & Sari, 2022). It can be concluded that students prefer learning in the form of using Kahoot media than using media with quizizz.…”
Section: Introductionmentioning
confidence: 64%
“…Hasil penelitian tentang Kahoot dalam pembelajaran, disajikan dalam bentuk tabel, sebagai berikut: Hasil pemaparan tabel 1 menunjukkan bahwa penggunaan gamifikasi dalam pembelajaran berdampak positif dalam meningkatkan pemahaman, pengetahuan, keterampilan, sikap (Fadhli, Muhibuddin et al, 2020), menjadikan pembelajaran lebih menyenangkan (Zahara et al, 2021). Gamifikasi dengan menggunakan aplikasi kahoot dalam pembelajaran di SD lebih diminati daripada aplikasi quizizz (Fadly & Sari, 2022), Pembelajaran dengan Kahoot mendapatkan respon yang baik (Perdana et al, 2020), berpengaruh terhadap kemampuan berifkir kritis, penguasaan konsep, (Mertayasa et al, 2022), dapat meningkatkan motivasi, dan hasil belajar siswa, (Tumurang & Chandra, 2023). Pemanfaatan gamifikasi kahoot bisa di kombinasikan dengan model, metode atau pendekatan lain (Isamiati & Nabar, 2023), (Rahmawati, 2023), serta bisa digunakan dalam pembelajaran online (Tumurang & Chandra, 2023).…”
Section: Gamifikasi (Kahoot) Dalam Pembelajaran DI Sd/miunclassified
“…Fadly (2022) researched students' perceptions of the Kahoot application, entitled "Student Perceptions of Using Kahoot and Quizizz in Learning in Fourth-Grade of Elementary Schools." This study used a quantitative descriptive research methodology and a survey design.…”
mentioning
confidence: 99%